Precipitation and encapsulation of β-sitosterol using supercritical antisolvent (SAS) method for controlled nutraceutical release. - Romero-Figueroa, J (Elsevier Ltd, 2026)
β-sitosterol (βsit) is a plant-derived phytosterol with recognized health-promoting properties, but its low aqueous solubility and limited bioavailability constrain its use in nutraceuticals and functional foods. This study aimed to precipitate and encapsulate βsit within polycaprolactone (PCL) using the Supercritical AntiSolvent (SAS) process in order to develop a controlled delivery system for nutraceutical bioactives. First, βsit was precipitated from a 2% ethyl acetate solution at 40 °C and pressures ranging from 9 to 13 MPa to identify suitable operating conditions; 9 MPa was selected as optimal due to its lower βsit solubility in the CO2/solvent mixture. These conditions were then applied for the precipitation of βsit with PCL. The SAS mechanism relied on the anti-solvent action of supercritical CO₂, promoting rapid precipitation and the formation of βsit:PCL microparticles. The inclusion of Tween 80 (T80) enhanced incorporation efficiency, promoted uniform microparticle morphology, and increased overall process yield. Formulation variables modulated both the release kinetics and underlying mechanisms. Incorporation within PCL slowed βsit release, while T80 accelerated it, likely due to reduced matrix crystallinity. Overall, βsit was successfully micronized along with PCL using SAS-based precipitation, highlighting its potential for the combination of bioactive compounds in functional foods and nutraceutical applications. © 2026 The Authors